(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Sashi Deshpande (born 1938) is an Indian novelist. Born in Dharwad, Karnataka, the second daughter of actress and writer from Kannada Adya Rangacharya and Sharada Adya. He studied in Bombay (now Mumbai) and Bangalore. Deshpande holds degrees in Economics and Law. In Mumbai, he studied journalism at Vidya Bhavan and worked for a few months as a journalist for Onlooker magazine. He published his first collection of short stories in 1978, and his first novel, ’The Dark Holds No Terror’, in 1980. He won the Sahitya Akademi Award for the novel Long Silence in 1990 and the Padma Shri Award in 2009. His novel Shadow Play was nominated for The Hindu Literary Prize in 2014. Deshpande has written four children’s books, many short stories, and nine novels, with the exception of several sharp essays, published in a volume entitled Writing from the Margin and Other Essays. On October 9, 2015, he resigned from the Sahitya Akademi General Assembly and returned his Sahitya Akademi award. In doing so, he joined a widespread protest by some writers against the work of the Academy and his silence on M’s assassination. M. Kalburgi. On December 6, 2018, in his inaugural address to the ninth edition of the Goa Arts and Literature Festival (GALF), Deshpande urged Indians to consider the consequences of seeking the Hindu nation, and reminded those present of the violence and genocide that had resulted from India and Pakistan’s divisions.